The Effect of Flipped Classroom Learning Model on Psychomotor Learning Outcomes in Prototype Design for Class X Students at SMK Negeri 1 Sawit Boyolali - Lucky Alexander Darmawan; Fatma Sukmawati; Rahma Alya Radisty (Universitas Sebelas Maret, 2026)
This study examines the effect of the Flipped Classroom learning model on psychomotor learning outcomes (prototype design skills) of Class X Automotive Engineering students at SMK Negeri 1 Sawit Boyolali. This research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of 71 students: Class X TO 2 (n=35) as the experimental group receiving Flipped Classroom instruction, and Class X TO 4 (n=36) as the control group using Guided Discovery. Data were collected through performance assessment using a rubric covering five aspects of prototype design: tools usage, layout, element selection, innovation, and theme suitability. Data analysis included descriptive statistics, normality and homogeneity tests, Independent Sample t-Test, and Cohen's d effect size. Results indicated that the experimental group achieved a higher average post-test score (78.57) and N-Gain (0.391) compared to the control group (76.81; N-Gain 0.334). However, the Independent Sample t-Test yielded t = 0.675 (p = 0.502 > 0.05), indicating no statistically significant difference. Cohen's d = 0.160 revealed a small effect size. Despite this, descriptive analysis showed that the Flipped Classroom model produced more evenly distributed improvements, with 54.29% of experimental students achieving moderate N-Gain compared to only 30.5 6% in the control group. This study concludes that although the Flipped Classroom model has not produced statistically significant differences, it demonstrates promising potential in enhancing the quality and equity of psychomotor learning outcomes in vocational education.